Pharmaceutical Formulation Strategy Approach from Red Palm Oil (Elaeis guineensis Jacq) - Andre Alwi Azhari; Mahdi Jufri; Heri Setiawan (Eduvest - Journal of Universal Studies, 2025)
Red palm oil (RPO) comes from the mesocarp of the palm fruit (Elaeis guineensis Jacq.) which is rich in carotenoids, vitamin E, and fatty acids. The use of RPO in pharmaceutical formulations poses challenges related to stability, oxidation susceptibility, and consumer acceptance due to its distinctive aroma and taste. To address these limitations, a variety of innovative formulation strategies, including emulsification, nanoemulsification, microencapsulation, and lipid-based systems have been researched. The RPO formulation aims to improve stability, bioavailability, and enhance therapeutic effects. Manufacturing techniques such as high-pressure homogenization, spray drying, and encapsulation of supercritical fluids have stabilized the bioactive components of RPO, minimizing oxidation, and controlling continuous release. Nanoemulsions and lipid nanoparticles have shown results in a wide range of applications from topical antioxidants to systemic drug delivery, by utilizing the synergistic effects of the lipophilic properties of RPO with other active ingredients. In addition, encapsulation technology has improved the stability of RPO storage, thereby expanding its usefulness in nutraceuticals and multivitamin supplements. This article also aims to bridge the research gap related to RPO formulation and provide insights into optimizing RPO formulations for broader benefits in health and disease management. The use of RPO in the future perspective is focused on nanotechnology formulations to improve solubility, stability, bioavailability, and support targeted and controlled drug delivery.